Recognition and assessment of resident' deterioration in the nursing home setting: A critical ethnography. Issue 7 (24th April 2018) - Laging, Bridget; Kenny, Amanda; Bauer, Michael; Nay, Rhonda
Abstract : Aims and objectives: To explore the recognition and assessment of resident deterioration in the nursing home setting. Background: There is a dearth of research exploring how nurses and personal‐care‐assistants manage a deteriorating nursing home resident. Design: Critical ethnography. Methods: Observation and semi‐structured interviews with 66 participants (general medical practitioners, nurses, personal‐care‐assistants, residents and family members) in two Australian nursing homes. The study has been reported in accordance with the Consolidated Criteria for Reporting Qualitative Research guidelines. Results: The value of nursing assessment is poorly recognised in the nursing home setting. A lack of clarity regarding the importance of nursing assessments associated with resident care has contributed to a decreasing presence of registered nurses and an increasing reliance on personal‐care‐assistants who had inadequate skills and knowledge to recognise signs of deterioration. Registered nurses experienced limited organisational support for autonomous decision‐making and were often expected to undertake protocol‐driven decisions that contributed to potentially avoidable hospital transfers. Conclusions: Nurses need to demonstrate the importance of assessment, in association with day‐to‐day resident care and demand standardised, regulated, educational preparation of an appropriate workforce who are competent in undertaking this role. Workforce structures that enhance familiarity between nursing home staff and residents could result in improved resident outcomes. The value of nursing assessment, in guiding decisions at the point of resident deterioration, warrants further consideration.